Metaverse and Virtual Worlds of Science - Sheka, Elena F (Trends in Computer Science and Information Technology, 2024)
Information is presented on the emergence of a new meaning for the existence of the human community, which could be characterized by the word “hyperrealization”. Virtual worlds of digital twins, digital ecosystems, quasi-metaverse, and, finally, the metaverse – this is the path that everything existing in the world, including science, must take.